Clinical Approach to Assessment and Amelioration of Atherosclerotic Vascular Disease in Diabetes - Goldberg, Ronald B. (Frontiers in Cardiovascular Medicine, 2020)
Atherosclerotic cardiovascular disease is increased on average 2-3 fold in people with diabetes as compared to their non-diabetic counterparts and is the major cause of the increased morbidity and mortality in this disease. There is however heterogeneity in cardiovascular risk between individuals based on demographic, cardiometabolic and clinical risk factors in the setting of hyperglycemia, insulin resistance and obesity that needs to be taken into consideration in planning preventive interventions. Randomized clinical trials of agents or procedures used for amelioration of augmented CVD risk in diabetes have been pivotal in providing evidenced-based treatments. Improvement in hyperglycemia in both type 1 and type 2 diabetes is considered to be central in the prevention of microvascular and macrovascular complications although selected antihyperglycemic agents have demonstrated beneficial as well as possible deleterious off-target effects. Lowering low density lipoprotein cholesterol, treating hypertension and stopping smoking each play important roles in preventing cardiovascular disease in diabetes as they do in the general population and low dose aspirin is overall beneficial in high risk individuals. Hypertriglyceridemia may represent another important marker for augmented cardiovascular risk in diabetes and newer agents targeting dyslipidemia appear promising. The fall in cardiovascular events over the past two decades offers hope that modern intervention strategies as well as novel approaches such as those targeting inflammation may contribute to a continued reduction of cardiovascular disease in people with diabetes.